An innovative green material for reducing the urban heat island surrounding PMU towards smart low carbon building and city - Dzulkifli N.A.; Omar R.C.; Abidin A.H.Z.; Roslan R.; Wahab W.A.; Baharuddin I.N.Z.; Sanusi K.A. (Science and Engineering Research Support Society, 2023)
In this study, a new innovative green material using waste material especially vegetable waste and their combination was developed to be used as PMU streetscape furniture. It is has been tested based on the international green material standard. In line with the deliverable of new material to be used as PMU streetscape furniture, exploratory study of combination used of waste material using vegetable waste or name as Vege-grout coating give a good promise and comply with the standard for improvement of streetscape surrounding the PMU facades. Based on the results, it is found that the best way to reduce the surface temperature of the paver block is by immersing the paver block in Vege-grout and paint mixture. Using this method, heat is reduced up to 7C. Building information modeling (BIM) result shows reducing of heat up to 12C from the facades of surrounding streetscape material used. The results showed an improvement in the thermal conductivity test for pavement coating based on The American Society for Testing and Materials (ASTM) describes methods for determining solar reflectance in the following standards; ASTM E 903, ASTM E 1175, ASTM C 1549 and ASTM E 1918. 2019 SERSC.